2016
DOI: 10.1152/ajpendo.00240.2015
|View full text |Cite
|
Sign up to set email alerts
|

Heightened TWEAK-NF-κB signaling and inflammation-associated fibrosis in paralyzed muscles of men with chronic spinal cord injury

Abstract: McLain AB, Oster RA, Bamman MM. Heightened TWEAK-NF-B signaling and inflammation-associated fibrosis in paralyzed muscles of men with chronic spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 45 publications
1
37
1
Order By: Relevance
“…Data are presented as means ± 95% confidence intervals were no changes in the mRNA expression of IL-6, TNFα, or TWEAK. These elevations were seen together with greater Fn14 and activated NF-κB-p65 protein expression and further suggest greater inflammation sensitivity in paralyzed muscle (Yarar-Fisher, Bickel, & Kelly, 2016). Our current data conflicts with our previous study in mice in which we reported an upregulation of pro-inflammatory cytokines in the gastrocnemius of paralyzed mice following a complete spinal cord transection (Graham et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Data are presented as means ± 95% confidence intervals were no changes in the mRNA expression of IL-6, TNFα, or TWEAK. These elevations were seen together with greater Fn14 and activated NF-κB-p65 protein expression and further suggest greater inflammation sensitivity in paralyzed muscle (Yarar-Fisher, Bickel, & Kelly, 2016). Our current data conflicts with our previous study in mice in which we reported an upregulation of pro-inflammatory cytokines in the gastrocnemius of paralyzed mice following a complete spinal cord transection (Graham et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…It is also an important transcription factor, which has a proinflammatory role in the inflammatory response and possesses a variety of biological functions (21,22). SCI activates NF-κB in glial, neural and vascular endothelial cells, causing the activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…A marked increase in vastus lateralis mRNA expression of TNFα-, TNF-like weak inducer of apoptosis (TWEAK)-and interleukin (IL)-6-family cytokines and receptors 5-days post burn injury suggests changes in inflammatory signaling may contribute to the observed atrophy (Merritt et al, 2013b). Similarly, elevated expression of TWEAK and TNFα receptors has been observed in paralyzed muscle of men with chronic spinal cord injury, a condition that also presents with muscle atrophy and impaired regenerative capacity (Yarar-Fisher et al, 2016). The opposing regulatory roles of local inflammatory signaling in myogenesis and muscle mass maintenance indicate the post-injury or post-operative inflammatory response must be well-controlled to maintain muscle mass and allow for adequate tissue regeneration.…”
Section: Potential Consequences Of Heightened Intramuscular Inflammatmentioning
confidence: 99%